2011
DOI: 10.3386/w17239
|View full text |Cite
|
Sign up to set email alerts
|

Over-optimism in Forecasts by Official Budget Agencies and Its Implications

Abstract: The paper studies forecasts of real growth rates and budget balances made by official government agencies among 33 countries. In general, the forecasts are found: (i) to have a positive average bias, (ii) to be more biased in booms, and (iii) to be even more biased at the 3-year horizon than at shorter horizons. This over-optimism in official forecasts can help explain excessive budget deficits, especially the failure to run surpluses during periods of high output: if a boom is forecasted to last indefinitely,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
3
14
1
Order By: Relevance
“…This result differs from that obtained by Merola and Pérez (2013), who found the good times dummy to be positive and significant, but is in line with those of Frankel (2011) and Frankel and Schreger (2013), who found that official forecasts were especially subject to wishful thinking during booms.…”
Section: Resultscontrasting
confidence: 96%
See 2 more Smart Citations
“…This result differs from that obtained by Merola and Pérez (2013), who found the good times dummy to be positive and significant, but is in line with those of Frankel (2011) and Frankel and Schreger (2013), who found that official forecasts were especially subject to wishful thinking during booms.…”
Section: Resultscontrasting
confidence: 96%
“…This result is consistent with the previous literature, which has found that the optimistic bias of public forecasts tends to increase as the horizon lengthens (Frankel, 2011;Frankel & Schreger, 2013, 2016. One reason for this might be an upward bias in GDP growth forecasts due to governments using GDP forecasts in a strategic manner.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…20 There is, besides, no obligation for budgetary projections, which are always produced by governments and only occasionally assessed by a fiscal council, because the ''comply or explain'' principle is not compulsory. Finally, no EU country employs macro projections from a panel of private sector forecasters, a more definite solution to insulate official forecasts from executive/legislature strategic interactions (Frankel 2011;Frankel and Schreger 2014).…”
Section: Econometric Estimatesmentioning
confidence: 99%
“…It is worth noting that the subset of models that relies on forecasts of GDP growth as a driver of health expenditure are subject to the potential error within those forecasts [54].…”
Section: Incomementioning
confidence: 99%